New stories from the South the year's best, 1987 - Ravenel, Shannon (Prince Frederick, MD : Recorded Books, 1987)
The 19th publication of this annual anthology delivers a collection of short fiction by various award-winning Southern writers and rising stars.
Title from container.
Unabridged.
In container (17 cm.).
Compact discs.
Performed by various narrators.
Keywords: Short stories, American -- Southern States; American fiction -- 20th century; Southern States -- Fiction